Volume 7B: Structures and Dynamics 2014
DOI: 10.1115/gt2014-26874
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Flutter Analysis of a Long Shrouded Steam Turbine Blade

Abstract: An advanced flutter analysis of a final stage turbine row with a new 1.2 meter long shrouded blade is presented. The three-dimensional (3D) unsteady Reynolds Averaged Navier-Stokes (URANS) equations with the Spalart and Allmaras turbulence model were employed to model the flow. The flow entering the last stage is a mixture of saturated vapor and liquid. An equilibrium wet-steam equation of state was used to model the properties of the mixture. Multi-row steady state simulations of the upstream stator row, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The acoustic wave reflection from the outlet of the computational domain can influence the predicted aeroelastic stability of turbomachinery [13,14]. Fortunately, the acoustics wave was cut-off for the least unstable IBPA analyzed in this paper, and thus, the impact of acoustic reflection on the aeroelastic characteristic would not be critical with the extended fluid domain in the flutter test case.…”
Section: Fluid Dynamicsmentioning
confidence: 91%
“…The acoustic wave reflection from the outlet of the computational domain can influence the predicted aeroelastic stability of turbomachinery [13,14]. Fortunately, the acoustics wave was cut-off for the least unstable IBPA analyzed in this paper, and thus, the impact of acoustic reflection on the aeroelastic characteristic would not be critical with the extended fluid domain in the flutter test case.…”
Section: Fluid Dynamicsmentioning
confidence: 91%
“…In this paper the flow is assumed to be as ideal gas with a ratio of specific heat of 1.12 and a dynamic viscosity of 1.032·10 −5 Pa·s, which is constant over the stage. It has been shown that this assumption is valid for steam turbine flutter calculations (Petrie-Repar et al, 2014).…”
Section: Test Case Definitionmentioning
confidence: 99%
“…In recent years, blade flutter risk has caught more attention because of the manufacturers interest to increase turbine output and improve performance level (Rice et.al, 2009). Three-dimensional unsteady inviscid (Masserey et.al, 2012 andRice et.al, 2009) and URANS (Stüer et.al, 2008 andPetrie-Repar et al, 2014) flow simulations for flutter analysis have been performed previously. However, the blade profiles and the flow properties presented by OEMs are always protected and kept as a secret.…”
Section: Introductionmentioning
confidence: 99%
“…The test case was run with an ideal gas with the parameters listed in Table 1. For a justification of the use of ideal gas for the flutter analysis of steam turbines, the reader is referred to [22]. Table 1.…”
Section: Test Casementioning
confidence: 99%